O Programa De Avaliação da Aprendizagem Escolar (PAAE) em Minas Gerais: interfaces entre práticas avaliativas e currículo de História no Ensino Médio - Alex de Oliveira Fernandes (2017)
The main goal of this study was to investigate the Programa de Avaliação da Aprendizagem Escolar (PAAE) [Evaluation Program of School Learning], implemented by Secretaria Estadual de Educação de Minas Gerais (SEE-MG) [Minas Gerais Department of Education], identifying its implications on the practices of History teaching. We intended to get to analyze the theoretical-methodological conceptions of evaluation and teaching-learning that guide the program and the ways of use of evaluation at the teaching practices of High School. As methodological approach we have adopted literature, documental and field review, which consisted of questionnaire application to History teachers, the observation of the use of evaluations, the analysis of content from curricular matrixes and of test items from exams generated by PAAE, and that are applied on the schools of the public state education system. We adopted as analytical categories the sociological approach of evaluation based on the contributions of Afonso (2009), in the search for interfaces on the contemporary debate on the relationship between evaluation, curriculum and teacher work. Under this perspective, evaluation becomes a privileged investigation field that allows for the analysis of nexus existent on the systems and models for state regulation, on the modalities bind to pedagogical conceptions, contexts and political and socioeconomic conjunctures. The results evince that the discourse of advantages and benefits promoted by the systems and evaluation programs lined on the educational management model inspired by accountability tends to hide the complexity intrinsic to the field of didactics, to the teaching-learning process, in favor to the reductionist conceptions of teaching, of a technicalist bias, disregarding the plurality of concepts and the multifaceted dimension of curriculum and of the practices of evaluation of school learning. Specifically in relation to PAAE, we have observed a contradiction between the announcement of the innovator character of the items used as pedagogical resource and the hegemonic present of traditional questions of History matter. We observed that such procedure have contributed to the maintenance of conservative postures on the evaluation practices, in detriment of the formative modality announced. The observation of the practices of use of the program by the teachers show that, as a public policy, PAAE has not achieved the results expected by the managers and idealizers. We also observed the distance between said and done about the conception of formative evaluation on High School. The program installed the culture of standardized tests, limiting the curricular perspective present on Currículo Básico Comum (CBC) [Common Basic Curriculum] of History matter.